MANAJEMEN PEMBELAJARAN BAHASA ARAB DI MADRASAH (Studi Kasus di MTsN 2 Muara Jambi) - Mulyadi (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2020)
Arabic learning management needs to be considered as carefully as possible so that the Arabic teaching and learning process can run effectively and efficiently. Learning Arabic in terms of one element of education management, namely encouragement or direction (actuating).In addition, it is also an effort to design active, creative and fun learning (active and joyful learning) in the classroom.Qualitative research is used to understand, look for the meaning behind the data, to find the truth, both sensual empirical truth, logical empirical, and ethical empirical. The purpose of qualitative research itself is to construct buildings in an idiographic, namely the effort to provide descriptions or special humans or individuals, there is no pretension to seek generalizations, at the most it provides insight into possible transferability.All components of Arabic learning at Madrasah Tsanawiyah Negeri 2 Muara Jambi are seen to be mutually integrative, synergistic and proportional. After conducting an analysis related to the management of learning Arabic in the classroom from the perspective of direction or support. In this case, the teacher has a strategy and way of sharpening his own learning. The teacher takes the role and model as providing direction and support for students in learning Arabic, including the teacher as a motivator, teacher teaching style and teacher leadership style in the classroom.